Symptom Assessment Training Based on Adult Learning Theory Evaluation of the Application Effect in Improving the Evaluation Ability of New Nurses in NICU: Adult learning theory Evaluation in improving ability of intern nurses - Wan, Xingli; Cheng, Hong; Wu, Yaohua; Li, Xia; Guo, Xuemei; Su, Shaoyu; Hu, Yanling; Chen, Qiong; Li, Xiaowen (Progress in Nutrition, 2021)
Objective: To improve the ability to assess the symptoms of new nurses in NICU by training them in symptom assessment. Methods:Based on adult learning theory, a training program for symptom assessment was developed and new NICU nurses were trained. The training effect was evaluated from three aspects: knowledge, skill and behavior. After the training, the new nurses’ satisfaction with the symptom assessment training was investigated. Results: A total of 34 new nurses completed symptom assessment training. Knowledge, training, training and after training after the end of march before scoring differences statistically significant (F = 100.632, p = 0.000), LSD test results show that the training after the examination scores and later before the training and training in March after the assessment score difference was statistically significant, but the training before and after the training ended march test score differences had no statistical significance; In terms of ability, the training professionals randomly checked the clinical symptom assessment skills of 10 persons before and after the training, and the difference in scores before and after the training was statistically significant (t=-5.489, p=0.000).In terms of behavior, the changes in symptom evaluation behavior of new nurses before and after the self-evaluation training showed that the behavior of new nurses after the training was significantly higher than that before the training, and the difference was statistically significant (p=0.000).The overall satisfaction of the new nurses with the symptom assessment training was 100%. Conclusion. The training of symptom assessment based on adult learning theory can effectively improve the assessment ability of new NICU nurses.